Analisis Kepuasan Pelanggan Terhadap Pelayanan Jasa Rumah Kost Dempo Di Kota Pontianak - Daved Hendrawan (JURNAL MANAJEMEN MOTIVASI, 2014)
This study aims to analyze customer satisfaction VIP boarding room against Dempo services Boarding House in Pontianak. The method used in this research is descriptive method. The population of this study is that all customers who rent a room in a boarding VIP Boarding House Dempo through 2013 amounted to 582 people with a total sample of 100 people were taken using purposive sampling, ie customers who have rented a VIP boarding room for at least one month and aged 20 years and over . This study uses five dimensions of service quality as a variable, namely reliability (reliability), responsiveness (responsiveness), assurance (assurance), empathy (empathy) and intangible (tangible) in which includes as many as 26 service attributes and measured using a Likert scale. The fifth dimension is used to measure customer satisfaction VIP boarding room against Dempo services Boarding House in Pontianak. The analysis tool is SERVQUAL (service quality). The results showed that the boarding room VIP customers are not satisfied with the services Dempo Boarding House in Pontianak because SERVQUAL scores (gap) is negative. This means that expectations (expectations) VIP customers boarding room is greater than the performance of services. SERVQUAL scores (gap) five dimensions of service is negative with dimensions of responsiveness (responsiveness) had the highest level of dissatisfaction and dimensions of reliability (reliability) has the lowest level of dissatisfaction. Service attributes that have the highest level of dissatisfaction is the speed of the employees in responding to and addressing any customer complaints VIP boarding room (dimensions of responsiveness) with a score of SERVQUAL (gap) the highest. While the service attributes that have the lowest level of dissatisfaction is the comfort of the VIP boarding room to be occupied (dimensions collateral) with a score of SERVQUAL (gap) the lowest.